2001
DOI: 10.1080/00380768.2001.10408440
|View full text |Cite
|
Sign up to set email alerts
|

Background levels of trace and ultra-trace elements in soils of Japan

Abstract: Five hundred and fourteen soil samples collected from 78 sites in Japan were analyzed for their contents of trace and ultra-trace elements. We estimated the background levels (natural abundance) of 57 elements in soils. The concentration ranges were so wide that the ratios of the highest values to the lowest values were more than 100 for all the elements, with the exception of Be, Ga, Mo, Ag, In, Sn, and Ba. While the concentrations of the first transition elements (2ISC to soZn in atomic numbers) were higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 8 publications
3
29
3
Order By: Relevance
“…Kinshozan soils, comparisons with average compositions of Japanese soils (Yamasaki 2001) and the upper continental crustal composition (Togashi et al 2000) were made (Table 1 and Figure 2). Compared with the average Japanese soils, those on limestone bedrock tend to be rich in Al 2 O 3 and Fe 2 O 3 , and depleted in MgO, CaO, and Na 2 O.…”
Section: Resultsmentioning
confidence: 99%
“…Kinshozan soils, comparisons with average compositions of Japanese soils (Yamasaki 2001) and the upper continental crustal composition (Togashi et al 2000) were made (Table 1 and Figure 2). Compared with the average Japanese soils, those on limestone bedrock tend to be rich in Al 2 O 3 and Fe 2 O 3 , and depleted in MgO, CaO, and Na 2 O.…”
Section: Resultsmentioning
confidence: 99%
“…Correlation coefficients were calculated using log-transformed values with the exception of those for aluminum (Al), silicon (Si) and iron (Fe), because the frequency distributions of all the other elements were close to log-normal distributions. As for the metallic trace elements in soils, Yamasaki et al (2001) showed that highly positive correlation coefficients (r > 0.8) were observed for a considerable number of combinations. In contrast, more than 80% of the absolute values of correlation coefficients for Br and I against 60 other elements were less than 0.4, indicating that the behavior of these elements in the terrestrial environments could be entirely different from that of most of the other metallic elements.…”
Section: Dependence Of Br and I Concentrations On Soil Horizonsmentioning
confidence: 99%
“…A somewhat similar trend was observed for agricultural soils, though the difference between upland soils and paddy fields was much narrower. Table 6 shows the correlation coefficients of Br and I against 60 other elements obtained from analytical data for mainland soils (Yamasaki et al 2001;Takeda et al 2004). As for the results of other groups of samples, the numbers of analyzed elements were not as large as those of mainland soils, and therefore were not included in this attempt.…”
Section: Dependence Of Br and I Concentrations On Soil Horizonsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the concentrations of Zr in the soils were relatively high, the correlation was not so good. That could be attributed to the incomplete decomposition of zircon (ZrSiO 4 ) under the soil decomposition process for the ICP-MS measurement (Yamasaki et al 2001;Tsukada et al 2005;Matsunami et al 2010). Although high correlation coefficients were observed for Cd and Pb, one of the soil samples had remarkably high concentrations and possibly made the coefficients higher than those in lower concentration ranges (Fig.…”
Section: Concentrations Of Other Trace Elements In Soilmentioning
confidence: 99%